Estimating Movement Smoothness From Inertial Measurement Units - Melendez-Calderon, Alejandro; Shirota, Camila; Balasubramanian, Sivakumar (Frontiers in Bioengineering and Biotechnology, 2021)
There is an increasing trend in using inertial measurement units (IMUs) to estimate movement quality and quantity, and infer the nature of motor behavior. The current literature contains several attempts to estimate movement smoothness using data from IMUs, most of which assume that the translational and rotational kinematics measured by IMUs can be directly used with existing smoothness measures - spectral arc length (SPARC) and log dimensionless jerk (LDLJ-V). However, there has been no investigation of the validity of these approaches. In this paper, we systematically evaluate the appropriateness of the using these measures on the kinematics measured by an IMU. We show that: (a) current measures (SPARC and LDLJ-V) are inappropriate for translational movements; and (b) SPARC and LDLJ-V can be used rotational kinematics measured by an IMU. For discrete translational movements, we propose a modified version of the LDLJ-V measure, which can be applied to acceleration data (LDLJ-A), while roughly maintaining the properties of the original measure. However, accuracy of LDLJ-A depends on the IMU orientation estimation error. We evaluate the performance of these measures using simulated and experimental data. We then provide recommendations for how to appropriately apply these measures in practice, and the various factors to be aware of when performing smoothness analysis using IMU data.